2000
DOI: 10.1001/archinte.160.8.1154
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Effects of a High–Monounsaturated Fat Diet Based on Macadamia Nuts

Abstract: Background: Recent studies have identified potential beneficial effects of eating nuts, most of which have substantial amounts of monounsaturated fats. Macadamia nuts are 75% fat by weight, 80% of which is monounsaturated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(101 citation statements)
references
References 22 publications
5
86
1
6
Order By: Relevance
“…[69] Similarly, It was observed that 4 weeks macadamia oil supplementation reduced total cholesterol and LDL cholesterol and increased HDL cholesterol in hypercholesterolemic men (n = 17), at the same time palmitoleic (C16:1n-7), vaccenic (18:1n-7), and eicoseinoic (C20:1n-9) acid levels were enhanced. [70] It is important to mention that, although macadamia oil or a macadamia-rich diet has been observed to be an efficient nonpharmacological treatment of hypercholesterolemia, [69][70][71][72] the effects have been attributed to palmitoleic acid rather than other fatty acid components. A randomized, crossover, controlled feeding study that compared the fatty acid content and effects of a macadamia-rich diet and an average American diet observed that while palmitoleic acid amounts increased six times with the macadamiarich diet, the other MUFAs were very similar between the diets.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…[69] Similarly, It was observed that 4 weeks macadamia oil supplementation reduced total cholesterol and LDL cholesterol and increased HDL cholesterol in hypercholesterolemic men (n = 17), at the same time palmitoleic (C16:1n-7), vaccenic (18:1n-7), and eicoseinoic (C20:1n-9) acid levels were enhanced. [70] It is important to mention that, although macadamia oil or a macadamia-rich diet has been observed to be an efficient nonpharmacological treatment of hypercholesterolemia, [69][70][71][72] the effects have been attributed to palmitoleic acid rather than other fatty acid components. A randomized, crossover, controlled feeding study that compared the fatty acid content and effects of a macadamia-rich diet and an average American diet observed that while palmitoleic acid amounts increased six times with the macadamiarich diet, the other MUFAs were very similar between the diets.…”
Section: Referencementioning
confidence: 99%
“…Palmitoleic acid versus oleic acid diet-palmitoleic acid diet: ↑ total cholesterol, ↑ LDL cholesterol, ↓ HDL cholesterol [71] Subjects (n = 30, aged 18-53) fed with three diets for 30 d in a random order: a "typical American" diet (12% MUFA); an American Heart Association Step 1 diet (15% MUFA); or a macadamia nut-based monounsaturated fat diet (20% MUFA) (randomized crossover trial)…”
Section: Referencementioning
confidence: 99%
“…iet and lifestyle modifications have long been advocated to decrease the risk of cardiovascular disease (CVD) (1), which is one of the main causes of death worldwide (2). Dietary fatty acids of varying chain length and degree of saturation differentially alter plasma lipoprotein profiles and the subsequent risk of developing CVD.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] However, their use is not yet part of standard advice for patients with hyperlipidemia, 12,13 despite recognized health benefits for the general population. 13 There is also concern that high-fat foods may cause weight gain.…”
mentioning
confidence: 99%